The Incidence and Demographic Distribution of Type 1 Diabetes_x000D_ Mellitus in Children Aged 16 or Younger Between 2000 and 2016 in_x000D_ Cyprus - (:unkn) unknown (My University, 2020)
diabetes in adults between 20-80 years of age in Cyprus but data regarding this incidence in the pediatric population is lacking. Theobjective of this study was to report the incidence of T1D among permanent inhabitants aged 16 years or younger between 2001-2016in Cyprus.Methods: This study was a retrospective analysis. The patients were mainly evaluated and recorded at Dr. Burhan Nalbantoğlu Hospital,Nicosia. Data was also reviewed from Famagusta Government Hospital, Kyrenia Government Hospital, Near East University Hospital andthe Cyprus Turkish Diabetes Association.Results: A total of 107 subjects were diagnosed as T1D between 2001 and 2016 in the pediatric age group. Forty-nine (45.7%) weregirls and 58 (54.3%) were boys. Of these 38.7% were resident in Nicosia, 30.2% Famagusta, 12.3% Kyrenia, 9.4% Guzelyurt and 7.5%Iskele. The proportion of newly diagnosed T1D was highest among children aged 9-12 years (35.5%) followed by children aged 5-8years (32.7%). Newly diagnosed T1D most frequently presented in March and April. The overall mean incidence rate was 11.1/100,000between 2001 and 2016. The incidence rates were similar and comparable among the years.Conclusion: This study is the first to analyze the incidence of T1D in Cyprus. Compared to other countries the incidence rate isintermediate. Our findings are similar to the incidence rates of T1D in South Cyprus and Turkey.